Perceived Stress Is Associated With Incident Coronary Heart Disease and All‐Cause Mortality in Low‐ but Not High‐Income Participants in the Reasons for Geographic And Racial Differences in Stroke Study. Issue 6 (19th December 2013) - Redmond, Nicole; Richman, Joshua; Gamboa, Christopher M.; Albert, Michelle A.; Sims, Mario; Durant, Raegan W.; Glasser, Stephen P.; Safford, Monika M.
Abstract : Background: Perceived stress may increase risk for coronary heart disease (CHD) and death, but few studies have examined these relationships longitudinally. We sought to determine the association of perceived stress with incident CHD and all‐cause mortality. Methods and Results: Data were from a prospective study of 24 443 participants without CHD at baseline from the national Reasons for Geographic And Racial Differences in Stroke (REGARDS) study cohort. Outcomes were expert‐adjudicated acute CHD and all‐cause mortality. Over a mean follow‐up of 4.2 (maximum 6.9) years, there were 659 incident CHD events and 1320 deaths. Analyses were stratified by income level because of significant interactions with stress. For individuals with low income, 3529 (35.4%) reported high stress, and for those with high income, 2524 (22.1%) did so. Compared with reporting no stress, those reporting the highest stress had higher risk for incident CHD if they reported low income (sociodemographic‐adjusted HR 1.36, 95% CI: 1.04, 1.78) but not high income (sociodemographic‐adjusted HR 0.82, 95% CI: 0.57, 1.16); the finding in low income individuals attenuated with adjustment for clinical and behavioral factors (HR 1.29, 95% CI: 0.99, 1.69, P =0.06). After full adjustment, the highest stress category was associated with higher risk for death among those with low income (HR 1.55, 95% CI: 1.31, 1.82) but not high income (HR 1.13, 95% CI: 0.88, 1.46). Conclusions: High stress was associated with greater risks of CHD and death for individuals with low but not high income.